2022
DOI: 10.1093/schbul/sbac148
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Therapy and COVID-19: A Systematic Review of the Prevalence Rates, Health Outcomes, Hematological Markers, and Patient Perspectives

Abstract: Background/Objectives There have been concerns that clozapine treatment may undermine the capacity of the body to fight infection and increase the vulnerability to contracting COVID-19. This review of recent cohort studies investigated (1) whether people with a severe psychiatric disorder are at increased risk of COVID-19 and complications, (2) the immunological response of clozapine-users who contract COVID-19, and (3) patients’ perspectives on COVID-19 and the pandemic response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 71 publications
1
20
0
1
Order By: Relevance
“…Although incidence rates were higher than reported in previous studies, all cases of mild neutropenia were likely related to infection with COVID-19. 9 This is consistent with evidence that the risks of neutropenia and agranulocytosis are very low after 1 year of treatment. 6,10 In fact, more recent data, including meta-analyses, have challenged the notion that clozapine poses an increased risk of neutropenia compared with conventional antipsychotics.…”
Section: Haematological and Clinical Outcomessupporting
confidence: 87%
See 2 more Smart Citations
“…Although incidence rates were higher than reported in previous studies, all cases of mild neutropenia were likely related to infection with COVID-19. 9 This is consistent with evidence that the risks of neutropenia and agranulocytosis are very low after 1 year of treatment. 6,10 In fact, more recent data, including meta-analyses, have challenged the notion that clozapine poses an increased risk of neutropenia compared with conventional antipsychotics.…”
Section: Haematological and Clinical Outcomessupporting
confidence: 87%
“…8 The importance of these recommendations has since been emphasised by recent evidence associating clozapine use with an increased risk of COVID-19 infection which, in some cases, results in clozapine intoxication. 9
Fig. 1Summary of the UK Medicines & Healthcare products Regulatory Agency (MHRA) guidelines for clozapine monitoring frequency (white cell count and absolute neutrophil count) and the emergency 12-weekly monitoring protocol.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors support the previously suggested 9,83 interference of COVID-19 in clozapine metabolism. 91 The main limitation of our study was not determining clozapine plasma concentration after the vaccination. Other limitations were the small sample size and the duration of observation, which might have prevented us from finding other consequences of COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 93%
“…The authors support the previously suggested 9,83 interference of COVID-19 in clozapine metabolism. 91…”
Section: Discussionmentioning
confidence: 99%